Fabrication of 1D ZnO nanostructures on MEMS cantilever for VOC sensor application - Kilinc, Necmettin; Cakmak, Onur; Kosemen, Arif; Ermek, Erhan; Ozturk, Sadullah; Yerli, Yusuf; Ozturk, Zafer Ziya; Urey, Hakan (ELSEVIER SCIENCE SA, 2014)
This study reports the fabrication method and sensing performance for novel 1D zinc oxide (ZnO) nanorods and nanotubes grown on nickel MEMS cantilevers. The fabrication of the nanostructures and the cantilevers are simple and low-cost using standard lithography, electrodeposition, and hydrothermal etching processes. 1D ZnO nanostructures increase the total sensitive area for biological and chemical sensor applications. We performed experiments with various VOCs with a real-time sensor system developed in our laboratory. While Ni microcantilevers produced no signal, ZnO nanostructure coated microcantilevers showed good sensitivity and repeatable changes. Furthermore, the nanotube coated microcantilevers showed more than 10 fold increase in sensitivity compared to the nanorod coated microcantilevers which can be explained to the fact that ZnO nanotubes have higher surface area and subsurface oxygen vacancies and these provide a larger effective surface area with higher surface-to-volume ratio as compared to ZnO nanorods. The tests are performed using dynamic mode of operation near resonant frequency using magnetic actuation and optical sensing. The phase stability and the limit of detection of ZnO nanotube coated microcantilevers exposed to diethylamine (DEA) were 0.02 degrees and lower than 10 ppm, respectively. ZnO nanostructure coated microcantilevers have good potential for VOC sensor applications especially for amine groups. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Microelectromechanical systems; Chemical sensors; VOC sensing; Zinc oxide; Nanorods; Nanotubes; GAS-SENSING PROPERTIES; SENSITIVE DETECTION; SINGLE-CHIP; ZINC-OXIDE; MICROCANTILEVER; NANOWIRES; ELECTRODEPOSITION; HYDROGEN; ARRAYS; Chemistry; Electrochemistry; Instruments & Instrumentation